Effectiveness of general practice nurse interventions in cardiac risk factor reduction amongst adults - Halcomb, E.; Moujalli, S.; Griffiths, R.; Davidson, Patricia (Blackwell Publishing Asia, 2007)
Background: Cardiovascular disease is the leading cause of death for adults in Australia. In recent years there has been a shift in health service delivery from institutional to community-based care for chronic conditions, including cardiovascular disease. The general practice setting is seen to offer greater flexibility, higher levels of efficiency and more client focused healthcare delivery than is possible in the acute care sector. It has been suggested that practice nurses represent a useful adjunct to current models of cardiovascular disease management. To date, significant descriptive research has been conducted exploring the demographics, roles, educational needs and issues facing practice nurses. However, there is a need to evaluate the effectiveness of practice nurse interventions in terms of patient outcomes, clinician satisfaction and cost-effectiveness. Objectives: This review seeks to present the best available evidence regarding the efficacy of general practice nurse interventions for cardiac risk factor reduction in healthy adults, as well as those with established cardiovascular disease or known cardiac risk factors. Search Strategy: A systematic literature search was performed using Medline (1966 – 2005), CINAHL (1982-2005), Cochrane Controlled Trials Register (Issue 4, 2005) and the Joanna Briggs Institute Evidence Library. In addition, the reference lists of retrieved papers, conference proceedings and the Internet, were scrutinised for additional trials. Selection Criteria: This review considered any English language randomised trials that investigated interventions conducted by the practice nurse for cardiovascular disease management or reduction of cardiac risk factors. Interventions conducted by specialist cardiac nurses in general practice were excluded. Outcomes measured included blood pressure, smoking cessation, total cholesterol, exercise, body weight/body mass index and cost-effectiveness. Results: Eighteen trials, reported in 33 papers, were included in the review. Ten trials investigated multifaceted interventions, while the remaining eight trials reported targeted interventions. Of the trials that reported multifaceted interventions, three trials investigated risk reduction in those with established cardiovascular disease, four trials focused on those with known cardiovascular disease risk factors and three trials included the general community. The eight trials which examined the efficacy of targeted interventions focused upon dietary intake (two trials), smoking cessation (three trials), weight reduction (one trial) and physical activity (two trials). The effect of both the multifaceted and targeted interventions on patient outcomes was variable. However, both the multifaceted and targeted interventions demonstrated similar outcome trends for specific variables. Improvements were demonstrated by most studies in blood pressure, cholesterol level, dietary intake and physical activity. The variation in outcome measures and contradictory findings between some studies makes it difficult to draw definitive conclusions. Conclusions: While interventions to reduce cardiovascular disease risk factors have produced variable results, they offer significant potential to assist patients in modifying their personal risk profile and should be developed. The public health importance of these changes is dependant upon the sustainability of the change and its effect on the health outcomes of these individuals. Further well-designed research is required to establish the effectiveness of practice nurse interventions for cardiovascular disease management and risk factor reduction in terms of patient outcomes and cost-effectiveness.